2021
DOI: 10.21608/ejnh.2021.194458
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the effect of milk, licorice and tiger nut on stomach ulcer induced in rats

Abstract: Peptic ulcer is a disease affecting a large number of people, caused by various reasons including, NSAIDs and stress. Acute injury occurs more readily with aspirin. The extracts of milk,tigernut and licorice were evaluated for their activities against aspirin gastric ulcer induced in albino rats. Thirty male albino rats, with an average weight of 155-160g were used divided into five groups.6 rats each.All rats were fed basal diet and given free distilled water.Group (1) was left for the whole period of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…In addition, Momeni A. et al [23] in 2014 noted that G Glabra extract is as effective as bismuth in preventing Helicobacter pylori and recommended effective treatment with licorice extract for patients who cannot take bismuth. Hajiagha Mohammadi and others [25] in 2016 G. glabra adding licorice to a triple clarithromycin-based regimen increases Helicobacter pylori eradication, especially in the presence of peptic ulcer disease. Nugroho A. E. in own studies [26] Glycyrrhiza glabra showed antiulcerogenic effects by increasing mucin secretion and prostaglandin E2 release and decreasing leukotrienes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Momeni A. et al [23] in 2014 noted that G Glabra extract is as effective as bismuth in preventing Helicobacter pylori and recommended effective treatment with licorice extract for patients who cannot take bismuth. Hajiagha Mohammadi and others [25] in 2016 G. glabra adding licorice to a triple clarithromycin-based regimen increases Helicobacter pylori eradication, especially in the presence of peptic ulcer disease. Nugroho A. E. in own studies [26] Glycyrrhiza glabra showed antiulcerogenic effects by increasing mucin secretion and prostaglandin E2 release and decreasing leukotrienes.…”
Section: Introductionmentioning
confidence: 99%